Effects of plant functional traits on ecosystem services: a review - Quan Pan; Hua Zheng; Wang, Zhiheng; Zhi Wen; YanZheng Yang (Journal of Plant EcologyJournal of Plant Ecology, 2021)
Comprehensively understanding the mechanisms underlying the formation of ecosystem services is a prerequisite for maintaining the sustainable supply of ecosystem services. Plant functional traits directly participate in a variety of ecosystem processes, which in turn affect the supply of ecosystem services. Revealing the relationship between plant functional traits and ecosystem services is an important way to understand the formation mechanism of ecosystem services. Based on a systematic literature review, 86 papers on plant functional properties and ecosystem services were retrieved in the Web of Science database, and data for 466 pairs of plant functional traits and ecosystem services and 83 plant functional traits were collected. The current status of research on the relationship between plant functional traits and ecosystem services was revealed. Moreover, the main plant functional traits that affect different ecosystem services and their mechanisms underlying their impacts were also demonstrated. The results show that the research on the relationship between plant functional traits and ecosystem services mostly focuses on natural ecosystems such as grasslands and forests. Most of these studies focus on ecosystem products providing and supporting services, including biomass, net primary productivity, and soil fertility. Based on the impacts of plant functional traits on different ecosystem services, the plant functional traits can be clustered into five categories: soil-conservation-related traits, water-cycle-related traits, ecosystem- multifunction- related traits, product-providing-related traits, and pollination-biocontrol-related traits. The impacts of climate change, human activities, and variations in spatial and temporal scales on the relationship between plant functional traits and ecosystem services need to be further explored.